PERAN POLA ASUH ORANGTUA DI ERA DIGITAL - Aslan, Aslan (Jurnal Studia Insania, 2019)
Technological developments are increasingly rapid in the digital age today, causing the values that are born, both positive and negative also experience a tremendous surprise for humans. From these surprises, so the role of parents in educating their children also changes by the development of their times. In the 80, parents in educating their children must have experienced a difference in the digital age today. The parenting style that initially experienced differences from other parents, which only applied authoritarian, permissive, democratic types of parenting, had experienced success in educating children, but in the age of the digital era, the three parenting styles would not succeed, if they did not synchronize according to the time of the situation and conditions in terms of parenting.